2017
DOI: 10.1007/s00281-017-0631-3
|View full text |Cite
|
Sign up to set email alerts
|

Synovial cellular and molecular markers in rheumatoid arthritis

Abstract: Summary The profound alterations in the structure, cellular composition and function of synovial tissue in rheumatoid arthritis (RA) are the basis for the persistent inflammation and cumulative joint destruction that are hallmarks of this disease. In RA the synovium develops characteristics of a tertiary lymphoid organ, with extensive infiltration of lymphocytes and myeloid cells. Concurrently the fibroblast-like synoviocytes undergo massive hyperplasia and acquire a tissue-invasive phenotype. In this review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 100 publications
0
48
0
Order By: Relevance
“…This is followed by the onset of clinical disease with inflammatory responses towards the synovial cells of the joints . Citrullination is a post‐transcriptional modification catalyzed by peptidylarginine deiminases (PADI) in which positively charged arginine residues are converted into neutral citrullines . This modification can generate different epitopes to which the immune system is intolerant, and trigger the immune reaction against citrullinated antigens .…”
Section: Ra Triggers and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is followed by the onset of clinical disease with inflammatory responses towards the synovial cells of the joints . Citrullination is a post‐transcriptional modification catalyzed by peptidylarginine deiminases (PADI) in which positively charged arginine residues are converted into neutral citrullines . This modification can generate different epitopes to which the immune system is intolerant, and trigger the immune reaction against citrullinated antigens .…”
Section: Ra Triggers and Pathogenesismentioning
confidence: 99%
“…Activation of immune inflammatory responses in RA cause synovial vascular inflammation and joint swelling, which is caused by leukocyte migration from the vasculature and infiltration into the synovium . The cellular composition of synovitis in RA includes both innate and adaptive immune cells such as monocyte‐lineage cells, dendritic cells, mast cells, osteoclasts, type 1 and 17 T‐helper cells, B‐cells and plasma cells . A robust tissue response by synovial fibroblasts together with enhanced chondrocyte catabolism and synovial osteoclastogenesis promotes articular destruction …”
Section: Ra Triggers and Pathogenesismentioning
confidence: 99%
“…93 Recent evidence, using animal models, shows that in an environment with inhibition of the endogenous p53, the invasiveness and proliferation of FLS were increased, suggesting a possible presence of somatic mutation in the p53 gene that could play an important role in the hyperplasia and cartilage damage generated by these cells. 59 One of the proposed pathways for the activation of these FLS is through chemokines, which have an influence not only on cell migration as previously believed, but also on gene transcription of some cells. Immune cells are not the only ones that express chemokine receptors, considering that several tissue cells can express them, including FLS.…”
Section: Other Cellsmentioning
confidence: 92%
“…It has been observed that the proportion of CD68-positive MCs is correlated with the radiological progression of the disease. 59 The interaction between monocytes, MCs, and ACPA has been clarified in recent years. ICs that contain citrullinated proteins, specially fibrinogen, and ACPAs are potent stimulants of TNF-alpha production by MCs, through FcyR IIa receptor.…”
Section: Macrophagesmentioning
confidence: 99%
“…However, in the case of RA, FLS cells display pleomorphic changes and undergo tumor like proliferation, giving it an aggressive phenotype leading to inflammation, joint destruction, and pannus formation (Turner & Filer, ). Under inflammatory micro‐environment, RA‐FLS majorly secrete inflammatory cytokines (TNFα, IL‐1β, and IL‐6), inflammatory mediators (COX‐2 and iNOS) and effector molecules (RANKL, GM‐CSF, and IL‐23) (Asif Amin, Fox, & Ruth, ; Bustamante et al, ). Various cytokines synergistically promote the proliferation and survival of RA‐FLS cells in the synovium (Rockel & Kapoor, ).…”
Section: Introductionmentioning
confidence: 99%